Medidas preventivas en la disminución de los riesgos de caídas en adultos mayores del geriátrico de Guaranda, período mayo – agosto 2024. - Carbo Álava, Clara Thanina (2024)
The study seeks to determine the most effective preventive measures to reduce the risks of falls in older adults in the Guaranda nursing home. It uses a non-experimental, descriptive and transversal methodology with a mixed (quantitative-qualitative) approach. Structured surveys and semi-structured interviews will be applied to 30 residents and 10 staff members of the nursing home to collect data on the incidence of falls, risk factors, and effectiveness of preventive measures. The data will be analyzed with statistical software and qualitative techniques, guaranteeing compliance with ethical principles such as informed consent and confidentiality.